Teanum und Campanien, Italien: Hellenistische Altäre und Heiligtümer - Wolf, Markus (e-Forschungsberichte des DAI, 2023)
The starting point of the new study is a Hellenistic altar at Teanum which can be reconstructed as a monumental altar with a triglyph/metope frieze and parapets with volutes which points to strong influences from the colonies of the Western Greeks. The building of Teanum is discussed in a comparative research within the wider context of Hellenistic altars and sanctuaries in Campania, where particularly a comparable altar of the Fondo Patturelli at Capua is a clear parallel. Both altars are influenced still by Greek ritual ideas, whereas in other sanctuaries Roman-Italian elements become increasingly characteristic.